2021
DOI: 10.1007/s00784-021-03988-4
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of periodontitis and orthodontic tooth movement—an in vitro and in vivo study

Abstract: Objectives The aim of this in vitro and in vivo study was to investigate the interaction of periodontitis and orthodontic tooth movement on interleukin (IL)-6 and C-X-C motif chemokine 2 (CXCL2). Materials and methods The effect of periodontitis and/or orthodontic tooth movement (OTM) on alveolar bone and gingival IL-6 and CXCL2 expressions was studied in rats by histology and RT-PCR, respectively. The animals were assigned to four groups (control, periodo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
2
19
0
3
Order By: Relevance
“…Using our in vivo experimental setup to simulate physiological pressure and overload on hPDL fibroblasts during OTM, we were able to demonstrate that after both 16 and 24 h of cell stimulation, a significant increase in IL-6 expression occurred at both magnitudes of mechanical stimulation. Tension on the other hand had no significant effect on IL-6 levels, as demonstrated earlier (Rath-Deschner et al, 2021). Thus, our results suggest that the mode of mechanical stimulation rather than stimulation intensity influences the expression of this cytokine in hPDL fibroblasts.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Using our in vivo experimental setup to simulate physiological pressure and overload on hPDL fibroblasts during OTM, we were able to demonstrate that after both 16 and 24 h of cell stimulation, a significant increase in IL-6 expression occurred at both magnitudes of mechanical stimulation. Tension on the other hand had no significant effect on IL-6 levels, as demonstrated earlier (Rath-Deschner et al, 2021). Thus, our results suggest that the mode of mechanical stimulation rather than stimulation intensity influences the expression of this cytokine in hPDL fibroblasts.…”
Section: Discussionsupporting
confidence: 78%
“…Our research group has previously shown that inducing OTM using a 25 gram nickeltitanium coil, over a period of 3 days, resulted in an increased expression of IL-6 in rats. However, this upregulation was not found to be statistically significant (Rath-Deschner et al, 2021). A significant increase in IL-6 expression was shown in OTM experiments with mice using higher force intensities (Mo and Hua, 2018).…”
Section: Discussionmentioning
confidence: 81%
“…Orthodontic treatment with fixed appliances induces an aseptic pseudo-inflammatory response [ 19 , 20 ]. An increase of pro-inflammatory cytokines correlates with periodontal destruction [ 22 27 ] and orthodontic treatment can reinforce dysbiotic inflammatory periodontal disease with IL-6 playing a key role [ 119 ]. Probiotics seem to induce immunomodulatory effects by (i) strengthening the innate immune response, (ii) promoting the production of anti-inflammatory cytokines, and by (iii) inhibiting pro-inflammatory cytokines [ 40 44 ] 117 105 , 120 .…”
Section: Discussionmentioning
confidence: 99%
“…A total of three sections was selected from each tooth from four animals in each group. The area of unmineralized tissue in the furcation region was determined by histomorphometric analysis as previously described [ 53 ]. A ROI comprised of a 1000-μm zone under the furcation roof of the maxillary first molar was studied.…”
Section: Methodsmentioning
confidence: 99%